2022
DOI: 10.1177/03611981221094822
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Cooperative Adaptive Cruise Control on Traffic Stability

Abstract: Cooperative adaptive cruise control (CACC) is one of the popular connected and automated vehicle (CAV) applications for cooperative driving automation with combined connectivity and automation technologies to improve string stability. This study aimed to derive the string stability conditions of a CACC controller and analyze the impacts of CACC on string stability for both a fleet of homogeneous CAVs and for heterogeneous traffic with human-driven vehicles (HDVs), connected vehicles (CVs) with connectivity tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…In recent years, the research on CACC mainly focuses on longitudinal single-lane control, including stability analysis [ 30 , 31 , 32 , 33 , 34 ], communication problem analysis [ 35 , 36 , 37 , 38 ], heterogeneous problem analysis [ 39 , 40 , 41 , 42 ], etc. The control algorithm is mainly aimed at improving the original single-vehicle control algorithm, such as PID control, sliding mode control, and distributed model predictive control.…”
Section: Related Workmentioning
confidence: 99%
“…In recent years, the research on CACC mainly focuses on longitudinal single-lane control, including stability analysis [ 30 , 31 , 32 , 33 , 34 ], communication problem analysis [ 35 , 36 , 37 , 38 ], heterogeneous problem analysis [ 39 , 40 , 41 , 42 ], etc. The control algorithm is mainly aimed at improving the original single-vehicle control algorithm, such as PID control, sliding mode control, and distributed model predictive control.…”
Section: Related Workmentioning
confidence: 99%
“…Studies have shown that human drivers in CAV platoons adjust their maneuvers, frequently decreasing their time headways [10,11]. Nevertheless, scenarios characterized by diminished reaction times of human drivers may lead to collisions [12].…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon is well known for its criticality and there is considerable ongoing research aimed at finding possible solutions to address the concern. A common belief is that such a shortcoming can only be addressed by allowing vehicles to communicate with each other, thus anticipating the onboard perception system reaction time ( 9 , 10 ). Such connectivity-enhanced solutions are commonly known as cooperative ACC (CACC) and rely on either vehicle-to-vehicle (V2V) or vehicle-to-infrastructure (V2I) wireless communication technologies.…”
mentioning
confidence: 99%
“…Such connectivity-enhanced solutions are commonly known as cooperative ACC (CACC) and rely on either vehicle-to-vehicle (V2V) or vehicle-to-infrastructure (V2I) wireless communication technologies. CACC has been studied in several works both via microscopic simulation ( 9 , 1113 ) and real-world campaigns ( 14 , 15 ). However, despite the huge potential behind the technology, real-world market adoption is largely undermined by cybersecurity threats, lack of infrastructure, and data privacy ( 16 , 17 ) and data ownership ( 18 ) concerns, which makes the theoretical benefit not attainable in the foreseeable future.…”
mentioning
confidence: 99%